POTRET KELUARGA DALAM KARYA LUKIS - IRVAN BASTEN ARWAN, Drs. Idran Wakidi,M.Pd, Drs. Abd. Hafiz,M.Pd (Serupa The Journal of Art Education, 2014)
The family is the basis of the formation of aperson's character. What happens outside the family environment is the result of the family's own up bringing. Family is defined as a complete system consisting of father, mother, and child. In spite of it all, the family sometimes forget the things that are most important educationis mutual understanding between the needs of family members, ie, a family whose members have lived the principles democratic values grounded in the principles of independence, equality, and mutual accept.This thesis aims to present a family figure in realist painting with oil media on canvas, revealing events in everyday life that unconsciously affect the survival of humans into the painting, giving families the knowledge to the community. The author sees this problem just a question of how to understand andhow to communicate. After the author tries to open to the family, a lot of things that writers get, starting from the experience of family members, counsels that inspired the author tobe better in life.Keywords : Potret, Family, Paiting Art